Exploring sex differences in lung cancer risk among workers in Ontario, Canada's Occupational Disease Surveillance System - Sritharan, Jeavana; Christopher, Gabriella; Eros, Fanni R.; Demers, Paul A. (Frontiers in Environmental Health, 2023)
This paper is highly relevant within the context of the special section on occupational cancer surveillance systems, as it presents important findings from a unique system known as the Occupational Disease Surveillance System (ODSS) in Ontario, Canada. It is one of a kind in Canada, containing information on both work and health outcomes. It has been successful in linking administrative health data to occupational information to understand cancer and other diseases among approximately 2.37 million workers. To date, few studies have explored the relationship between occupation and lung cancer risk in females compared to males in the same occupations. The focus of this paper is to examine sex differences in lung cancer risk in the ODSS, with an emphasis on female workers. Findings from this paper demonstrate that females in various traditional high-risk occupations had elevated risks for lung cancer consistent with males in the same occupations. Our study also observed higher lung cancer risks among females than males in certain occupations, emphasizing sex-based differences in lung cancer risk. Given some of the limitations of the study, the findings should be interpreted with caution. Overall, the ODSS demonstrates the ability to identify lung cancer risk by sex and occupation, helping fill the knowledge gap on lung cancer sex differences and highlighting high-risk occupation groups among females.